Co-digestion of organic and mineral wastes for enhanced biogas production: Reactor performance and evolution of microbial community and function. (15th March 2019) - Shamurad, Burhan; Gray, Neil; Petropoulos, Evangelos; Tabraiz, Shamas; Acharya, Kishor; Quintela-Baluja, Marcos; Sallis, Paul
Highlights: Mineral wastes utilised for optimising anaerobic digestion of MSW. Effects of two feeding methods on the anaerobic digestion were studied. Mineral wastes increased methane yield and provide digestion stability. Mineral wastes did not affect microbial diversity but accelerated bacterial growth. Contrastingly, feeding methods had large effects on the diversity of methanogens. Abstract: Mineral wastes (MWs) from municipal solid waste incineration plants and construction demolition sites are rich in minerals, heavy metals and have acid neutralising capacity. This renders such MWs a promising source of bulk and trace elements to enhance and stabilize biogas production in anaerobic processes. However, finding a MW with typical heavy metal concentrations, which promotes anaerobic digestion (AD) without adverse effects on the microbial community of the reactor is of major importance. To investigate the impact of several MW additives (1. incineration bottom ash; 2. fly ash; 3. boiler ash; 4. cement-based waste) as AD co-substrates, six 5 L single stage mesophilic, continuously stirred tank reactors (CSTR) were setup. Two different feeding regimes were employed including: (a) a liquid-recycled feeding method (LRFM); (b) a draw-and-fill feeding method (DFFM). Under the LRFM regime, one gram MW per gram organic waste enhanced process stability (pH), increased methane production (25–45% increase), and yielded (450–520 mL CH4 /g VS); DFFM enhanced digestibility to a lesser degree. Illumina HiSeq 16S rRNA community sequencing of reactors showed that the microbial community compositions were unaffected by the presence of MW additives in comparison to unamended controls, but MW amendment accelerated bacterial growth (determined by qPCR). In contrast, different feeding regimes altered the microbial communities; Methanoculleus (hydrogenotrophic) and Methanosaeta (acetoclastic) were the most abundant methanogenic genera in the LRFM reactors, and the more metabolically versatile Methanosarcina genus dominated under DFFM.